Magnetic and plagioclase linear fabric discrepancy in dykes: a new way to define the flow vector using magnetic foliation - Geoffroy, L. (2014)
In basaltic dykes the magnetic lineation K1 (maximum magnetic susceptibility axis) is generally taken to indicate the flow direction during solidification of the magma. This assumption was tested in Tertiary basaltic dykes from Greenland displaying independent evidence of subhorizontal flow. The digital processing of microphotographs from thin sections cut in (K1, K2) planes yields the preferred linear orientation of plagioclase, which apparently marks the magma flow lineation. In up to 60% of cases, the angular separation between K1 and the assumed flow direction is greater than 45degrees. This suggests that the uncorroborated use of magnetic lineations in dykes is risky. A simple geometrical method is proposed to infer the flow vector from AMS in dykes based solely on magnetic foliations.